The association between abortion experience and postmenopausal suicidal ideation and mental health: Results from the 5th Korean National Health and Nutrition Examination Survey (KNHANES V) - Jeong Ha Wie; Su Kyung Nam; Hyun Sun Ko; Jong Chul Shin; In Yang Park; Young Lee (Elsevier, 2019)
Objective: The association between abortion and postmenopausal mental health has not been clearly established in Asian women. The objective of this study was to evaluate the effect of abortion experiences on suicidal ideation and mental health in Korean postmenopausal women. Materials and methods: This study included 5133 postmenopausal women registered in the Korean National Health and Nutrition Examination Survey between 2010 and 2012. Difference in suicidal ideation according to type and number of abortions was analyzed. We used survey multiple logistic regression analysis to evaluate the effect of abortion experiences on the risk for suicidal ideation expressed as adjusted odd ratios (ORs) with 95% confidence intervals (95%CIs). Results: The risk of suicidal ideation was significantly higher in women who experienced more than three abortions (27.9%). While the incidence of suicidal ideation was not significantly affected by the number of spontaneous abortions (p = 0.718), suicidal ideation was significantly more frequent in women who had undergone ≥ three abortions (p = 0.003). After adjusting for demographic confounding factors, women who underwent ≥ three induced abortions had higher risk for suicidal ideation (OR: 1.510; 95% CI: 1.189-1.919; p = 0.031). This risk remained elevated even after controlling for depression (OR: 1.391; 95% CI: 1.1086-1.871, p = 0.002). Moreover, the risk of experiencing a depressive mood in daily life was also increased with increasing number of induced abortions even after controlling for depression (OR: 1.657; 95% CI: 1.274-2.156, p = 0.002). Conclusion: Undergoing three or more induced abortions during reproductive age was associated with postmenopausal suicidal ideation, stress, and depression. However, such association was not noted in those with spontaneous abortion, even in women with more miscarriages. Thus, clinicians should evaluate depression and suicidal ideation in women with multiple induced abortions. Keywords: Abortion, Spontaneous, Menopause, Suicidal ideation